IJCM_135A: Tobacco Burden, Legal Awareness, and Attitudes toward Control Measures among Healthcare Students, Professionals, and Staffs: Insights of an Online Survey in Bihar & Jharkhand, India - Biswas Bijit; Varshney Saurabh; Jahnavi G.; Narasimha Venkata Lakshmi; Nath Santanu; Venugopal Vinayagamoorthy; Ayub Arshad; Alam Benazir; Kumar Ujjwal; Jha Niwedita (Wolters Kluwer Medknow Publications, 2024)
Background: Healthcare professionals, students, and workers are vital change agents in the global battle against tobacco. Yet, it's important to note a concerning trend: there's a high prevalence of tobacco use among them in India, although data on this is limited. Objective: This study aimed to assess tobacco use prevalence, awareness of related laws, and attitudes among healthcare professionals, students, and staff in Bihar and Jharkhand, India. Methodology: In July and August 2023, we conducted an extensive cross sectional, online survey across 24 tertiary healthcare institutions. Participants included a diverse group of medical, dental, and nursing students, faculty, resident physicians, nursing professionals, and support staff. The survey covered sociodemographic factors, tobacco use, awareness of laws (26 items) [a: 0.924), compliance practices (9 items) (a: 0.929), and perceptions of tobacco control (10 items) (a: 0.728). Results: Our research revealed a significant prevalence of tobacco use: 15.9% reported current use, with 9.6% as daily users. Notably, awareness levels differed noticeably between users and non-users, with non-users displaying deeper knowledge of tobacco-related laws in 61.5% of cases. Our multifactor logistic regression models for current (R2: 0.184, PAR: 84.1%) and daily tobacco use (R2: 0.203, PAR: 90.4%) highlighted various associated factors, including age, gender, marital status, occupation, family income, and native state. Importantly, insufficient awareness emerged as a key factor, correlating with higher chances of current and daily tobacco use. Regional differences were evident, with lower prevalence in southern states. A majority of faculty (90.0%) and students (93.6%) expressed the need for increased emphasis on tobacco control in healthcare curricula. Conclusion: Our research highlights disparities in healthcare tobacco use, influenced by age, gender, marital status, occupation, income, and location. Awareness plays a crucial role, emphasizing the need for integrating tobacco education into curricula and sustaining awareness campaigns to address this issue effectively